CALCULATION STUDIES OF SPATIAL DISTRIBUTION OF THE ABSORBED DOSE RATE FOR VARIOUS SEEDS - N. A. Nerozin; A. P. Pyshko; V. V. Shapovalov (Исследования и практика в медицине)
Purpose. Conducting computational studies of dosimetric characteristics of microsources with the radionuclide I‑125, pilot production of which is established in the research and production complex of isotope and radiopharmaceuticals, JSC “State Scientific Centre of the Russian Federation — Institute for Physics and Power Engineering named after A. I. Leypunsky” (SSC RF IPPE). Sources of production IPPE are similar to the model 6711 of the company Nicomed Amersham, dosimetric characteristics of which are standardized in accordance with the TG43 AAPM formalism.Materials and methods. Microsourse «SEED No. 6711» (model of the company Nicomed Amersham) is hermetically sealed in a titanium capsule silver rod covered with a thin layer of radioactive I‑125. The half-life of iodine‑125 is 59,43 days. In the process of decay of I‑125 is converted into the Te‑125.Calculation of parameters of microsources and their comparison with the standard model 6711 is carried out with use of the computer code MCNP.Results. The method of calculation of the basic dosimetric characteristics of the microsourse SSC RF-IPPE in accordance with the TG43 formalism is developed. A comparative analysis of experimental data and calculated results by MCNP code, which allowed to identify possible reasons for differences, is performed. The estimated dose characteristics and recommended standard data for dose characteristics of micro «SEED No. 6711» are compared.Conclusions. There are two possible reasons for the differences between experimental and calculated results. The first one may be the roughness of the surface of a silver rod or diffusion of radioactive iodine in silver. The second reason might be the difference of the cross sections of the characteristic radiation of silver used in MCNP code. In the comparison of calculated dose characteristics and recommended standard the role of the application activity is very important. In compliance with the standard conditions on the composition of the environment, water phantom and air with 40% humidity, the results obtained are outside the acceptable difference of 3% from the recommended data. While the variation of only the thickness of the deposition of radioactive material in the 0–10 mkm change dosimetric characteristics in the range of 15–20%.